How travel motivation and engagement can boost loyalty to wellness tourism in Yogyakarta - Wulan Octavianto Fatihah; Prima Nurita Rusmaningsih (Jurnal Pariwisata Pesona, 2023)
Wellness tourism is a type of special interest tourism that aims to maintain the body's fitness of tourists. Wellness tourism with facilities or activities that involve tourists, such as yoga, spas, and art performances. One of the fitness tourism destinations in Indonesia that is currently entering the development stage is the Special Region of Yogyakarta. These destinations have various kinds of local wisdom to be an attraction in terms of attractive fitness tourism activities. This study was conducted to analyze the effect of tourist motivation on destination loyalty (loyalty to destinations) through the involvement of tourists in wellness tourism in the Special Region of Yogyakarta. This study uses a quantitative approach, the type of explanatory research, by distributing questionnaires to 120 domestic tourists who visit fitness tourism destinations in the Special Region of Yogyakarta using a non-probability sampling technique with purposive sampling. The data analysis technique used is statistic descriptive, regression analysis, and Sobel Test which is used to see the influence between variables, either directly or indirectly. The results of this study indicate that there is an influence between tourist motivation and destination loyalty through the involvement of tourists in wellness tourism in the Special Region of Yogyakarta. In addition, the tourist involvement variable has a mediating role for the tourism motivation variable with destination loyalty.